Health Behavior, Health-Related Quality of Life, and Mental Health Among Canadian Children: A Population-Based Cohort Study - Wu, Xiuyun; Veugelers, Paul J.; Ohinmaa, Arto (Frontiers in Nutrition, 2021)
Objective: Studies that have reported associations of diet quality, physical activity (PA), sedentary behaviour (SB) and health-related quality of life (HRQoL) with mental health among children and adolescents are predominantly cross-sectional in design. Very few studies have examined the longitudinal relationship of mental health with the health behaviour and HRQoL among children. This study aimed to investigate associations of diet quality, PA, SB and HRQoL among children with mental health disorders throughout childhood. Methods: We linked data from grade five students aged primarily 10 and 11 years old who participated in the Raising healthy Eating and Active Living (REAL) Kids Alberta survey in 2012 in the Canadian province of Alberta with their administrative health care data from birth (2000) to 2012. Mental health outcomes included internalizing disorder and attention-deficit and hyperactivity disorder (ADHD) defined by the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) or Tenth Revision, Canadian version (ICD-10-CA). The HRQoL was measured by the EQ-5D-Y, a five-dimensional descriptive system for children and youth. We applied negative binomial regressions to examine the associations between the health behaviours, HRQoL and mental health. Results: Of the 1,352 participating students, 12.31% and 8.32% had a diagnosis of internalizing disorders and ADHDs respectively during childhood from birth to the ages of 10 to 11 years. Students in the highest tertile for diet quality, relative to the lowest tertile, were 56% less likely to have diagnoses for internalizing disorders (incidence rate ratio, IRR = 0.44, 95% CI: 0.23, 0.85. Students engaged in less PA (versus more PA) were more likely to be diagnosed for internalizing disorders (IRR = 1.98, 95% CI: 1.19, 3.30). Poorer diet quality, low PA, excessive use of computers/video games and watching TV were significantly associated with more diagnoses of ADHDs. Children who experienced some or a lot of problems in “feeling worried, sad or unhappy” and “having pain or discomfort” were more likely to receive diagnoses for internalizing disorders and ADHDs respectively. Conclusions: These observed associations suggest that health promotion programs targeting promoting diet quality, PA, HRQoL and reducing SB among children may contribute to improving mental health.